(untitled) (Historia, 2021)
The controversial appointment of C H Wessels as second administrator of the Orange Free State 1915-1924. Cornelis Hermanus Wessels’ appointment in 1915 as the second administrator of the Orange Free State, a position which he held until his death in 1924, was preceded by political upheaval which eventually led to the government’s decision to appoint a new administrator for the province. In 1914 Gen. L. Botha’s ruling South African Party (SAP) finally split as a result of policy differences between him and Gen. J.B.M. Hertzog. In that year Hertzog founded the National Party (NPI in which the majority of the white inhabitants of the Orange Free State, especially the Afrikaans speaking people, found their political home. The pro-Hertzog leanings of Dr. A.E.W. Ramsbottom, the first administrator, and the tactless manner according to Botha-supporters, in which he handled the Rebellion crisis in 1914, left the government with no choice but to replace him when his term of office expired in 1915. To Wessels, one of the few leading influential Free State political figures who were a sound government supporter, fell the honour of becoming Ramsbottom’s successor. Wessels found himself in an unenviable political situation, since he as a SAP administrator was faced with an overwhelmingly NP-orientated Provincial Council and an exclusively NP Executive Committee. Through his personality and fine political diplomacy, he neutralized the antagonistic feelings towards him in NP provincial circles and thereby established a sound administration. He succeeded in leading the Free State in an uncontroversial manner through a period of serious political economic and social problems.